SUMBER EPISTEMOLOGI & HUBUNGAN AL-QUR’AN DENGAN KEBENARAN (MEMAHAMI PESAN-PESAN KEBENARAN DALAM AL-QURAN) - Muhammad Ibrahim (Jurnal Dakwah Tabligh, 2015)
Epistemologically science is built on the basis of methodologies derived from the nature of reality that is believed to be true. epistemology of course determine the character of knowledge, even determine the truth What is considered acceptable and what should be rejected. When the body of knowledge which was classified, or arranged systematically with the correct method, then it can be epistemology. To further emphasize the importance of science, the Qur'an provides questions a test to them. Qur'an as a source of knowledge to justify the source of knowledge that has been discussed by philosophers such as emperisme, rationalism, intuition and revelation to note that all the sources of that knowledge to work in their respective areas. Qur'an as a book of instructions and guidelines on human life, of course covers a range of information that is scientific. Therefore, the Qur'an has a close relationship with science. Where the Qur'an provides the basics about science or the Qur’an laid the universality of science